Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How do I calculate the infinite sum of this series?

$$\sum_{n=1}^{\infty}n^2q^n = -\frac{q(q+1)}{(q-1)^3}\ \text{when}\ |q| < 1.$$

How does wolfram alpha get this result?

share|cite|improve this question
Which one of the above results do you mean? – Babak S. Jan 8 '14 at 12:16
Apparently, there was some unfortunate editing here.… – user3071205 Jan 8 '14 at 12:19
Did you mean this? – Michael Albanese Jan 8 '14 at 12:20
@user3071205: But this link is not the same as you added in the body. :-) – Babak S. Jan 8 '14 at 12:21
I rolled back the edit because it is better to have the formula here than to have a link to another site which displays it. – Michael Albanese Jan 8 '14 at 12:35
up vote 4 down vote accepted

$$ \sum_{n=1}^\infty n^2q^n=q\sum_{n=1}^\infty n^2q^{n-1}=q\cdot\frac{\text d}{\text dq}\left(\sum_{n=1}^\infty nq^n\right) $$ It is well-known that $\frac{1}{(1-x)^2}=\sum_{n=1}^\infty nx^{n-1}$ (given $|x|<1$), so we have \begin{align} \sum_{n=1}^\infty n^2q^n&=q\cdot\frac{\text d}{\text dq}\left(\frac q{(1-q)^2}\right)\\ &=q\cdot\frac{(1-q)^2+2q(1-q)}{(1-q)^4}\\ &=\frac{q(1+q)}{(1-q)^3} \end{align}

share|cite|improve this answer

A related problem. Recalling the series

$$ \sum_{k=1}^{\infty} q^k = \frac{q}{1-q} $$

Now, apply the operator $(qD)^2 = (qD)(qD) $ where $D= \frac{d}{dq} $ to both sides of the above equation.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.